Management of Anterior Choroidal Artery Aneurysms: A Retrospective Cohort Study - Andrew Falzon; Shigeta Miyake; Tze Phei Kee; Hugo Andrade-Barazarte; Timo Krings (Brain Sciences)
Background: Anterior choroidal artery (AChoA) aneurysms pose a challenge for both endovascular and clipping procedures. The eloquent territory supplied by the parent vessel has limited collateralization and its compromise can lead to significant morbidity. This study aims to analyze the clinical outcomes and procedure-related complications of clipping and endovascular treatment of AChoA aneurysms to aid physician decision making. Methods: Thirty-two ruptured and unruptured AChoA aneurysms that underwent catheter angiography at a single neurovascular center between January 2000 and December 2023 were included. Either conservative management, clipping, and/or endovascular treatment were performed. Clinical outcomes and complications were analyzed retrospectively. Results: Twenty-four endovascular treatments and seven clipping procedures were included. Of the total 24 endovascular procedures, 46% were primary coiling, 25% were balloon-assisted coiling, 13% were flow diverting stent, 8% were combined balloon-assisted coiling and flow diverting stent, and 8% were combined balloon-assisted and stent-assisted coiling. There was no procedure-related mortality in both groups. No intra- or post-procedural ruptures/re-ruptures occurred during follow-up in both endovascular and clipping cohorts. AChoA territory infarcts occurred in 4% of the endovascular and 29% of the clipping cohorts. Other thromboembolic complications occurred in 4% of the endovascular cohort. The recurrence rate requiring retreatment was 12.5% for the endovascular and 43% for the clipping cohort. A favorable clinical outcome (mRS ≤ 2) was 78% for the endovascular cohort and 67% for the clipping cohort. Conclusions: Endovascular and clipping outcomes align with prior studies, with endovascular showing a favorable safety profile. Both approaches are viable, though they present distinct risks and advantages.